2016
DOI: 10.1007/s12011-016-0783-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Copper, Iron, and Zinc Contents in Selected Indian (Assam) and South African (Thohoyandou) Tea (Camellia sinensis L.) Samples and Their Infusion: A Quest for Health Risks to Consumer

Abstract: The current study aims to assess the infusion pattern of three important micronutrients namely copper (Cu), iron (Fe) and zinc (Zn) contents from black tea samples produced in Assam (India) and Thohoyandou (South Africa). Average daily intakes and hazardous quotient were reported for these micronutrients. Total content for Cu, Fe and Zn varied from 2.25 to 48.82 mg kg-1, 14.75 to 148.18 mg kg-1 and 28.48 to 106.68 mg kg-1 respectively. The average contents of each of the three micronutrients were higher in tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…People here have a long‐standing habit of drinking tea. Studies have shown that tea leaves contain Cu, Zn, Fe, and a great quantity of organic acid which could inhibit the Ca absorption . Those may contribute to the elevated Cu and Zn levels and decreased Ca level in Lu'an.…”
Section: Discussionmentioning
confidence: 99%
“…People here have a long‐standing habit of drinking tea. Studies have shown that tea leaves contain Cu, Zn, Fe, and a great quantity of organic acid which could inhibit the Ca absorption . Those may contribute to the elevated Cu and Zn levels and decreased Ca level in Lu'an.…”
Section: Discussionmentioning
confidence: 99%
“…Values in parentheses indicate Legislation for MSWC addition in India . Values in square brackets represent the percentages of each fraction with respect to total soil Cd.…”
Section: Resultsmentioning
confidence: 99%
“…The ADI of Cd from tea infusion was assessed following the modified equation of the US EPA: ADI=true(normalC×normalDnormalItrue)/BW where ADI is the average daily intake (mg kg −1 bw per day, bw stands for body weight), C is the Cd concentration in tea infusion (mg L −1 ), DI is the average daily consume rate of tea infusion for Indian people (0.600 L day −1 ) when annual per capita consumption is 755.78 g/person per year, and BW is the average body weight with 67.4 and 64.9 kg for Indian men and women, respectively, (http://www.arogyadarpan.com/StandardHeightandWeightforIndianMenandWomen.aspx, accessed 3 March 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis may need to be supported by relevant biomarkers (i.e., hemoglobin, total iron-binding capacity, transferrin receptor and ferritin), which were not analyzed in this study. Poor blood Ca and Mg levels of the e-waste recyclers may be attributed to a higher intake of micronutrients such as Cu and Fe from their diet, which is believed to inhibit the absorption of Ca and Mg. For instance, at the e-waste scrapyard, recyclers have a long-standing habit of consuming a lot of tea and other herbs believed to contain Cu, Zn and Fe as well as organic acid, which are known to inhibit the absorption of Ca and Mg (Karak et al, 2017;Sembratowicz & Rusinek-Prystupa, 2014). In addition, the lower blood levels of Ca, Mg, Se and Fe among the e-waste recyclers may be related to their varied dietary habits and lower income status compared to the control population.…”
Section: Micronutrient Levels In Blood and Urine Of E-waste Recyclersmentioning
confidence: 99%